PERAN OTORITAS JASA KEUANGAN DAN PERLINDUNGAN HUKUM DEBITUR DALAM PERJANJIAN PEMINJAMAN BERBASIS TEKNOLOGI FINANSIAL (FINTECH) - Himawan Prasetyo (2021)
Financial technology (fintech) is a combination of technology and finance, the regulation of which is determined by the OJK. The problem in this research is how is the implementation of fintech-based lending and borrowing agreements regulated in Indonesian positive law? Another problem is what are the barriers to legal protection in the implementation of fintech lending and borrowing agreements? This study aims to determine the implementation of fintech agreements regulated in Indonesian positive law and also to find out the obstacles to legal protection in the implementation of fintech agreements. This research can be useful theoretically to contribute to the development of legal studies and practically provide benefits and knowledge for society in general. The research method used is normative research with a case approach and a statutory approach. Normative research is carried out by examining legal materials in the form of Law Number 8 of 1999 concerning Consumer Protection, Law Number 1 of 2009 concerning Aviation, and Supreme Court Decision Number: 975 K/Pdt/2019 which is the basic material to be studied using analysis which is qualitative. The results of this study are the implementation of fintech has been regulated by the OJK contained in POJK No. 77/POJK.01/2016 concerning Information Technology-Based Lending and Borrowing Services. The obstacles to legal protection in the implementation of fintech occur when the debtor defaults and the creditor commits an unlawful act, both of which occur because there is still a lack of legal protection arrangements in the OJK Regulation.